Determination of Maximum Accumulated Oxygen Deficit Using Backward Extrapolation - Andrade, Vitor Luiz; Kalva-Filho, Carlos Augusto; Ribeiro, Nayan Xavier; Gobbi, Ronaldo Bucken; de Arruda, Tarine Botta; Papoti, Marcelo (International Journal of Sports Medicine, 2020)
This study aimed to compare the Maximum Accumulated Oxygen Deficit determined by the conventional method (MAODC) with that determined by the backward extrapolation technique (MAODEXTR) in runners. Fourteen runners underwent a maximal incremental test for determination of iVO2MAX, ten submaximal efforts (50–95% of iVO2MAX for 7 min). During the submaximal efforts oxygen consumption (VO2) values were obtained conventionally and through the backward extrapolation technique (~ 3 s after the end of each effort). A supramaximal effort (110% of iVO2MAX) (tLimC) and five supramaximal bouts (tLimEXTR) were performed. MAODC and MAODEXTR were determined from the difference between the VO2 accumulated during tLimC and tLimEXTR and the predicted values. The tLimC was lower than tLimEXTR (164.06±36.32 s, 200.23±63.78 s, p<0.05). No significant differences were found between absolute and relative MAODC and MAODEXTR values, however, low intraclass correlations (0.26 and 0.24), high typical errors (2.03 L and 24 mL∙kg−1) were observed, and coefficients of variation (46 and 48%), respectively. The graphical analysis of the differences showed agreement and correlation between the methods (r=0.86 and 0.85). Thus, it can be concluded that the MAODEXTR is not a valid method for estimating the anaerobic capacity of runners, moreover, unreliable.
Keywords: runners; MAOD; anaerobic metabolism; anaerobic capacity